Strategies towards a sustainable fundraising model in schools: Lebowakgomo Circuit focus - Pudi, Mangoashe Victoria (My University, 2008)
Fundraising is operationally feasible in schools. Schools are allowed to solicit investors in terms of the South African School Act. The research was conducted at Lebowakgomo Circuit , Capricorn District. It was the purpose of this study to develop a sustainable fundraising model for schools through perceptions and experiences of the school principals. The researcher used a survey questionnaire to collect data. Statistical analysis were followed in order to derive information from the data. A key finding was that fundraising takes place at schools mostly when there is insufficient funds, organizing for school events or there is an urgent need of resources. Most of the schools do not allocate a budget for fundraising . A fundraising plan is not included in the school developmental plan. The plan for fundraising is done periodically when a need arises. The purpose and the size of the project determine the type of fundraising. Most of the businesses are willing to give as part of their social responsibility or tax cut. However, schools should market and sell themselves to potential donors and follow more aggressive strategies towards fundraising. Recommendations made include a sustainable fundraising model for schools and the steps to be followed when applying the model.
Thesis (MBA.) -- University of Limpopo, 2008
Keywords: Fund raising; Fund raising -- South Africa -- Limpopo; Educational fund raising